2010
DOI: 10.1016/j.finmar.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Financial distress and idiosyncratic volatility: An empirical investigation

Abstract: We investigate the link between distress and idiosyncratic volatility. Specifically, we examine the twin puzzles of anomalously low returns for high idiosyncratic volatility stocks and high distress risk stocks, documented by Ang et al. (2006) and Campbell et al. (2008), respectively. We document that these puzzles are empirically connected, and can be explained by a simple, theoretical, single-beta CAPM model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 18 publications
3
22
0
3
Order By: Relevance
“…integration has reduced the output volatility more in the case of developed countries as compared to developing countries. Our results support the findings of Kose et al (2003) and Chen and Wang (2009). Kose et al (2003) found that output volatility has declined in the 1990s as compared to previous periods, and Chen and Wang (2009) demonstrated that capital outflows reduced output and consumption volatility.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…integration has reduced the output volatility more in the case of developed countries as compared to developing countries. Our results support the findings of Kose et al (2003) and Chen and Wang (2009). Kose et al (2003) found that output volatility has declined in the 1990s as compared to previous periods, and Chen and Wang (2009) demonstrated that capital outflows reduced output and consumption volatility.…”
Section: Resultssupporting
confidence: 92%
“…First, financial integration measured based on both volume and equity has reduced output volatility for aggregate panel and panel based on income category (developed and developing countries). This result supports the findings of Kose et al (2003) and Chen and Wang (2009). Second, however, volume-based financial integration measurement has reduced the output volatility in all the regions except for Asia.…”
Section: Literature Reviewsupporting
confidence: 90%
See 1 more Smart Citation
“…However, market variables provide significantly more information about the firm's probability of bankruptcy than any accounting measures (Hillegeist et al. ), so the notion of market efficiency is supported as the most effective tool for forecasting bankruptcy (Chava and Jarrow ; Chen, Chollete, and Ray ; Xu and Zhan ). In some instances, studies on distressed firms are increased due to discrepancies in standard accounting criteria (Beaver, McNichols, and Rhie ).…”
Section: Previous Studies In Bankruptcy Problemsmentioning
confidence: 99%
“…Fifth, Chen et al . () argue that a firm with more volatile equity may experience an option effect, as it is more likely to reach the boundary condition for default. Lastly, in Barberis et al .…”
mentioning
confidence: 99%